2012
DOI: 10.1136/emermed-2012-201473
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in children presenting to the emergency department: a growing concern. Vitamin D deficiency in Birmingham's children: presentation to the emergency department

Abstract: Vitamin D deficiency should be considered in children with pigmented skin presenting with a range of symptoms. The detected vitamin D deficiency probably represents only a very small proportion of the vitamin D deficiency in children in Birmingham.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…A possible link between acute neonatal seizures, hypocalcemia and subsequent severe intellectual disability has been assessed in 149 adults with 22q11.2 deletion syndrome. 65 A history of neonatal seizures and neonatal hypocalcemia were significant predictors of a more severe level of intellectual disability, suggesting that neonatal seizures may increase the risk for more severe intellectual deficits in 22q11.2 deletion syndrome, likely mediated by neonatal hypocalcemia.…”
Section: Hypocalcemiamentioning
confidence: 99%
“…A possible link between acute neonatal seizures, hypocalcemia and subsequent severe intellectual disability has been assessed in 149 adults with 22q11.2 deletion syndrome. 65 A history of neonatal seizures and neonatal hypocalcemia were significant predictors of a more severe level of intellectual disability, suggesting that neonatal seizures may increase the risk for more severe intellectual deficits in 22q11.2 deletion syndrome, likely mediated by neonatal hypocalcemia.…”
Section: Hypocalcemiamentioning
confidence: 99%
“…Moreover, IBS patients had significantly lower mean 25OHD. In a pediatric ED setting, Kehler et al [36] identified 89 children with VDD, the majority (83%) with severe VDD. The most common clinical manifestation for ED admission was abdominal pain and the most common ethnic origins were black African and Pakistani.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective survey of children reported to be vitamin D insufficient (<50 nmol/l; <20 ng/ ml) in the United Kingdom, abdominal pain was the most common clinical feature (19%), with seizures and limb pain affecting around 16% of the children (Kehler et al, 2012). In Scotland, 160 cases of symptomatic vitamin D deficiency affecting infants and children aged 2 weeks to 14 years were identified between 2002 and 2008 (Ahmed et al, 2011).…”
Section: Childmentioning
confidence: 99%